Hard work, hidden lives : the short report of the Commission on vulnerable employment (London, 2008)
"This report highlights the key findings and recommendations of the Commission on Vulnerable Employment. It looks at the extent and impact of vulnerable employment in the UK, and proposes practical solutions to end exploitative treatment in work. The report covers awareness of employment rights in the UK, access to advice, enforcement of employment law and legal loopholes that prevent make unfair treatment permissible. It makes clear that trade unions, employers, civil society and government all have to act if vulnerable work is to end. "